The influence of exocyclic stereochemistry on the tethered aminohydroxylation reaction. - Donohoe, T; Lacy, A; Rathi, A; Walter, D (2011)
A new strategy that employs an exocyclic stereocenter to effect diastereocontrol in the tethered aminohydroxylation (TA) reaction is applied to the stereoselective synthesis of a range of amino alcohols in good to excellent yields, and with anti selectivities of up to 20:1. The influence of the reaction conditions and substrate parameters on the level of diastereocontrol is described. Furthermore, an "inside alkoxy" model is employed to rationalize the sense and degree of stereoselectivity observed in these systems.